Pengembangan Modul Pembelajaran Berorientasi Konstruktivisme pada Mata Diklat Merawat Alat Listrik Rumah Tangga (MALRT) - Rahmat Hidayat; Ricky Maulana; Nevi Faradina; Maulani Meutia Rani (Universitas Negeri Padang, 2023)
This development research aims to produce modules that are constructively oriented in training courses on caring for household electrical equipment, especially electrical installation techniques that are attractive and appropriate for use in learning, and to determine the effectiveness of the module in improving student learning outcomes. The advantages of this constructivism-oriented module are that it gives opportunities to students to be more active and independent in learning and building their knowledge, and can increase students' interest in participating in the learning process. The research and development design (Research and Development / R&D) with the 4D development model consists of 4 main stages, namely, Define, Design , Develop and Disseminate. Based on the findings of this study it was concluded that this module is valid, practical, and effective to be used as a learning medium in MALRT training courses for maintaining household electrical equipment majoring in electrical installation engineering at Vocational School, which can increase student motivation, activity, creativity and understanding so that it can have an impact increasing student learning outcomes. The implication of this research is that the module can provide input to the electrical engineering expertise program to continuously improve student competency.